ChemInform Abstract: Tetrahydropyranyl Ether (THPE) Formation in Hydroxyl Group Protection and Conversion to Other Useful Functionalities. Issue 37 (16th September 2014) - Kumar, Brijesh; Aga, Mushtaq A.; Rouf, Abdul; Shah, Bhahwal A.; Taneja, Subhash C.
Abstract Review: [164 refs.